Removal of Textile Dyes by Chemically Treated Sawdust of Acacia: Kinetic and Equilibrium Studies - Hanane Tounsadi; Yousra Metarfi; Noureddine Barka; Mustapha Taleb; Zakia Rais (Journal of Chemistry)
Sawdust of acacia tree has been successfully used to remove textile dyes from wastewater due to its good sorption properties and its good chemical stability. Two materials are prepared by chemical treatment, including acidic and basic sawdust of acacia. The biosorption tests were carried out on two synthetic dyes of textile which are methylene blue (MB) and brilliant blue (BB). Efficient removal of the both dyes has been achieved by the basic treated sawdust acacia. The modeling of biosorption kinetic shows that the biosorption of MB and that of BB are well described by the pseudo-first-order model for both the chemically treated biosorbents. Equilibrium data have also established using Langmuir and Freundlich isotherm models. Langmuir biosorption capacities are 8.13 and 267.04 mg/g onto basic sawdust acacia and 6.19 and 230.76 mg/g onto acidic sawdust acacia, respectively, for BB and MB sorption. A real final effluent of a textile industry was treated by sorption on both biosorbent basis of sawdust acacia. In fact, the kinetic sorption was rapid with a mass ratio of 1 g/L. However, the biosorption process combined with a biological treatment provides a better result through the physicochemical characteristics of the studied effluent.